Structure Relaxation Disruption on Temperature-dependence of Polymerization of HTPB-based Polyurethane - Afni Restasari; Nur Hamid; Leonard Marpaung; Andi Rusnaenah; Adi Sukma; Rahmawati Sukma (National Institute of Aeronautics and Space - LAPAN, 2021)
The temperature-dependence of polymerization rate of hydroxyl-terminated polybutadiene (HTPB)-based polyurethane can be disrupted by a structure relaxation of polymer. Objective of the study is to investigate the disruption on the polyurethane (PU) formed of various molecular weight of HTPB. The study was carried out by applying temperature of 50, 60 and 70 oC in measuring viscosity until 80 minutes of reaction. The sample that were used is HTPB with various molecular weight and Toluene diisocyanate (TDI). Based on decreasing value of viscosity, it is obtained that relaxation temperature of HTPB-based PU is around 60 – 70 oC. By applying Eyring equation of flow, it is found that relaxation of structure causes the existence of relaxation dominant-time (RDT). RDT is the reaction time at which molar volume reaches the maximum value. Furthermore, by determining activation entropy, the RDT was revealed to be a borderline between two type of polymerization. Linear reaction occurs before RDT, while cross-link reaction occurs after RDT. From structure point of view, PU-polymerization type of HTPB with low molecular weight tend to be more sensitive towards structure relaxation which is originated from hard segment.